2013
DOI: 10.1016/j.brs.2012.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Transcranial Direct Current Stimulation Modulates Verbal Working Memory

Abstract: Our results support the view that the cerebellum contributes to verbal working memory as measured by forward and backward digit spans. Moreover, the induction of reversible "virtual cerebellar lesions" in healthy individuals by means of tDCS may improve our understanding of the mechanistic basis of verbal working memory deficits in patients with cerebellar lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 33 publications
4
68
1
Order By: Relevance
“…Neuroimaging studies have found cerebellar activation during tasks involving language, emotion processing and executive function such as working memory (WM) [29,30]. Cerebellar involvement has also been found in the timing and coordination of motor responses [31], and there is emerging evidence that, in conjunction with other neural structures, the cerebellum may play a role in time processing [32,33], particularly in the sub-second range [34] and in rhythm learning [35].…”
Section: Cognitive Assessmentmentioning
confidence: 99%
“…Neuroimaging studies have found cerebellar activation during tasks involving language, emotion processing and executive function such as working memory (WM) [29,30]. Cerebellar involvement has also been found in the timing and coordination of motor responses [31], and there is emerging evidence that, in conjunction with other neural structures, the cerebellum may play a role in time processing [32,33], particularly in the sub-second range [34] and in rhythm learning [35].…”
Section: Cognitive Assessmentmentioning
confidence: 99%
“…Schmahmann’s cerebellar cognitive affective syndrome has shown that human cerebellar lesions cause cognitive impairments (Schmahmann, 2004). Inducing transient impairments using repetitive transcranial cerebellar stimulation has recently been shown to impair cognitive tasks such as language, emotion, learning, memory, perception, and timing (Fierro et al, 2007; Koch et al, 2007; Oliveri et al, 2007; Grube et al, 2010; Bijsterbosch et al, 2011; Boehringer et al, 2013; Tomlinson et al, 2013; Grimaldi et al, 2014). Similar deficits are reported following lesions to the anterior cingulate (Devinsky et al, 1995).…”
Section: Cingulocerebellar Interactions In Schizophreniamentioning
confidence: 99%
“…Several studies have found the cathodal TDCS to the cerebellum affected the performance of working memory tasks [84][85][86]. Finally, performance on a visuomotor adaptation task in healthy adults was improved by anodal TDCS [76].…”
Section: The Non-motor Role Of the Cerebellum In Dystoniamentioning
confidence: 99%
“…The left cerebellum has a greater role in visuospatial processing and in spatial working memory [78]. The right cerebellum is more associated with verbal working memory particularly when tested using a digit span working memory task [85] or the Paced Auditory Serial Subtraction Task (PASST) evaluating working memory and attention [86]. …”
Section: The Non-motor Role Of the Cerebellum In Dystoniamentioning
confidence: 99%